Formulation Development and Evaluation of Controlled Release Tablets of Famotidine - Jatav, Rajesh Kumar (International Journal of Pharmaceutical & Biological Archive, 2012)
Formulation Development and Evaluation of Controlled Release Tablets of Famotidine